Supportive Business Environments to Develop Grass Bioeconomy in Europe - Richard Orozco (MDPI AG, 2021)
Grasslands cover almost half of the total European agricultural area and are the source of a wide range of public goods and services. Yet, their potential to produce innovative bio-based products, such as paper and plastic, remains widely untapped. We employ a multiple case study approach and implement the Business Environment Framework by Adamseged and Grundmann (2020) on eighteen alternative grass-based businesses to investigate the interdependencies between these successful business models and their business environments. The subsequent analysis reveals that the deployment of funds and policies to support alternative grass-based products remains low in most regions of Europe. Our findings highlight that aligned funding mechanisms that incorporate and promote the specific benefits generated by grass-producing and grass-processing businesses are key to overcoming the barriers related to the competition of bio-based products with the established fossil-fuels-based economic system. To make alternative grass-based markets more dynamic, increasing consumer awareness through adequate marketing is perceived as an important aspect. Capacity building and alignment efforts need to be strengthened and coordinated at local and higher levels to enable the replication and scale-up of novel grass-based businesses in Europe and beyond.